Enrollment in HIV Care Two Years after HIV Diagnosis in the Kingdom of Swaziland: An Evaluation of a National Program of New Linkage Procedures. - Duncan A MacKellar (PLoS ONE, 2016)
To improve early enrollment in HIV care, the Swaziland Ministry of Health implemented new linkage procedures for persons HIV diagnosed during the Soka Uncobe male circumcision campaign (SOKA, 2011-2012) and the Swaziland HIV Incidence Measurement Survey (SHIMS, 2011). Abstraction of clinical records and telephone interviews of a retrospective cohort of HIV-diagnosed SOKA and SHIMS clients were conducted in 2013-2014 to evaluate compliance with new linkage procedures and enrollment in HIV care at 92 facilities throughout Swaziland. Of 1,105 clients evaluated, within 3, 12, and 24 months of diagnosis, an estimated 14.0%, 24.3%, and 37.0% enrolled in HIV care, respectively, after adjusting for lost to follow-up and non-response. Kaplan-Meier functions indicated lower enrollment probability among clients 14-24 (P = 0.0001) and 25-29 (P = 0.001) years of age compared with clients >35 years of age. At 69 facilities to which clients were referred for HIV care, compliance with new linkage procedures was low: referral forms were located for less than half (46.8%) of the clients, and few (9.6%) were recorded in the appointment register or called either before (0.3%) or after (4.9%) their appointment. Of over one thousand clients newly HIV diagnosed in Swaziland in 2011 and 2012, few received linkage services in accordance with national procedures and most had not enrolled in HIV care two years after their diagnosis. Our findings are a call to action to improve linkage services and early enrollment in HIV care in Swaziland.